Analisis Struktur Pasar Industri Rumah Tangga Sasirangan di Komplek Manarap Kabupaten Banjar - Syahrijal, Muhammad Rifqi; Aufa, Na’imatul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study focused on market structure analysis of home industry Sasirangan in Menarap, Kertak Hanyar, Banjarto determine market structure type. The purpose of the study to determine market structure and determine conditions of competition in sasirangan homeindustry. The method used is quantitative descriptive, which is research that is shown to describe the existing phenomena by using individual or group characteristic numbers. Technique are collecting questionnaire and documentation data. Data analysis techniques by knowing market share, market concentration of CR4 to know market structure. The results showed that the highest market share is Hai*** Craftsmen at 11.31%, and CR4 concentration ratio indicate that structure market Sasirangan in Menarap is Monopolistic Competetion with percentage ratio of 32.58%. The results of the study showed that the structure market is a Monopolistic Competetion with similar products but there is competition due to a slight differentiation in terms of quality and marketing.